2020
DOI: 10.1038/s41598-020-79160-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for yawn contagion in orangutans (Pongo pygmaeus)

Abstract: Yawning is highly contagious, yet both its proximate mechanism(s) and its ultimate causation remain poorly understood. Scholars have suggested a link between contagious yawning (CY) and sociality due to its appearance in mostly social species. Nevertheless, as findings are inconsistent, CY’s function and evolution remains heavily debated. One way to understand the evolution of CY is by studying it in hominids. Although CY has been found in chimpanzees and bonobos, but is absent in gorillas, data on orangutans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 93 publications
0
41
1
Order By: Relevance
“…Evolutionary biologists and neuroscientists have suggested that mammals, including humans, evolved laughing in response to tickling to signal submission to an attacker or to foster parent-child interactions, 79 , 80 and yawning can be useful in synchronizing the behaviour of a social group, for example, to get members of a heard to sleep at the same time. 81 While the benefit of yawning for humans seems obvious during childhood (i.e. parents are triggered to put their baby to sleep), adults often suppress the urge to yawn given its negative social stigma (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary biologists and neuroscientists have suggested that mammals, including humans, evolved laughing in response to tickling to signal submission to an attacker or to foster parent-child interactions, 79 , 80 and yawning can be useful in synchronizing the behaviour of a social group, for example, to get members of a heard to sleep at the same time. 81 While the benefit of yawning for humans seems obvious during childhood (i.e. parents are triggered to put their baby to sleep), adults often suppress the urge to yawn given its negative social stigma (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The automatic and reflexive tendency to yawn in response to sensing the yawns of others, i.e., contagious yawning, is well-documented in humans 1 , 2 , and has been observed in a growing number of non-human species including non-human great apes 3 , 4 , dogs 5 , pigs 6 , and birds 7 , 8 , among others. Unlike spontaneous yawning, which begins in utero 9 , is ubiquitous across vertebrates 10 , and appears to be a human universal 11 , contagious yawning does not emerge until early childhood 12 , 13 , is limited to social species 14 , and psychological studies reveal considerable variability in the tendency for people to yawn contagiously.…”
Section: Introductionmentioning
confidence: 99%
“…The possible relationship between oxytocin and yawn contagion is supported by evidence that yawn contagion in humans follows the empathic gradient (sensu Preston and de Waal 2002), being highest between closely bonded subjects (Norscia and Palagi 2011;Norscia et al 2020). Some features typical of mother-infant attachment, such as social recognition, bonding, and affiliation, are maintained in adulthood and promoted by oxytocin, which has been found to increase trust (Kosfeld et al 2005), generosity (Zak et al 2007), altruism (de Dreu et al 2010), and both cognitive and affective empathy (Rodrigues et al 2009;Shamay-Tsoory et al 2013;Smith et al 2014;Uzefovsky et al 2015). One of the future steps is to evaluate the possible covariation between oxytocin and yawn contagion in both pregnant and nulliparous women.…”
Section: Discussionmentioning
confidence: 96%
“…To the contrary, contagious yawning between conspecifics has been observed thus far in a relatively small number of species and may be an apomorphic trait, which appeared more recently in vertebrate evolution. With one exception (Pongo pygmaeus;van Berlo et al 2020), the species exhibiting yawn contagion between conspecifics usually live in highly social groups: namely, all the extant hominine species (chimpanzees: Anderson et al 2004;Campbell and Cox 2019;Campbell and de Waal 2011;bonobo, Pan paniscus: Demuru and Palagi 2012;Tan et al 2017; but see Amici et al 2014 on a very small sample size; humans: Provine 1986Provine , 1989, two species of cercopithecines (geladas and Tonkean macaques; Palagi et al 2009;, nonprimate mammals (lions, Panthera leo: Casetta et al 2021; wolves, Canis lupus lupus: Romero et al 2014;sheep, Ovis aries: Yonezawa et al 2017; elephant seals, Mirounga leonina: Wojczulanis-Jakubas et al 2019; domestic pigs, Sus scrofa: Norscia et al 2021), and one social bird species (budgerigar, Melopsittacus undulates: Gallup et al 2015).…”
mentioning
confidence: 99%